Constructing the Medical The saurus as a Tool for Indexing - Abuzir, Yousef (مجلة جامعة القدس المفتوحة للبحوث الإنسانية والاجتماعية, 2017)
There is an interest in extracting knowledge and retrieving information automatically from the current availability of a large collection of electronic resources and from the academic literature available on the Web. Much of Thus, researchers may miss relevant, even critical, information in parallel or disparate fields, which in turn may lead them to recreate information already developed or to miss important information that could advance each discipline. A Medical thesaurus identifies and clarifies important concepts from these disciplines and standardizes their corresponding terms. This paper reviews the structure, construction and use of Medical thesauri, and outlines how Medical Thesauri may help resolve a number of common difficulties encountered when searching these recourses. The increasing importance of the medical online resources as information resource makes the thesaurus an aid tool for both professionals and non-experts.